Sox5 regulates beta-cell phenotype and is reduced in type 2 diabetes - A. S. Axelsson (Nature Portfolio, 2017)
Type 2 diabetes (T2D) is a heterogeneous disorder characterized by insulin resistance and impaired insulin secretion. Here Axelssonet al. show that Sox5, which is reduced in diabetes, regulates a set of differentially expressed genes in T2D and its genetic and pharmacological induction improves insulin secretion by diabetic islets.